2021
DOI: 10.1210/clinem/dgab263
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid Immune-related Adverse Events Following Immune Checkpoint Inhibitor Treatment

Abstract: Background Thyroid dysfunction occurs commonly following immune checkpoint inhibition. The etiology of thyroid immune-related adverse events (irAEs) remains unclear and clinical presentation can be variable. This study sought to define thyroid irAEs following immune checkpoint inhibitor (ICI) treatment and describe their clinical and biochemical associations. Methods We performed a retrospective cohort study of thyroid dysfun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
127
2
6

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 128 publications
(147 citation statements)
references
References 26 publications
12
127
2
6
Order By: Relevance
“…Previously, it was suggested that treatment with VEGFi is an inducer of thyroid injury, increasing the risk for irT with CPI exposure [ 12 ]. While the rate of irT is higher in our cohort than the commonly reported 20–30% [ 7 , 8 , 10 , 12 , 18 , 19 , 20 ], the incidence rate did not differ between patients who were treated with immunotherapy in the first-line treatment or after previous treatment with VEGFi. For patients with previous thyroid dysfunction on VEGFi we found a non-significant trend of increased irT risk (HR = 2.14, p = 0.08).…”
Section: Discussioncontrasting
confidence: 87%
See 3 more Smart Citations
“…Previously, it was suggested that treatment with VEGFi is an inducer of thyroid injury, increasing the risk for irT with CPI exposure [ 12 ]. While the rate of irT is higher in our cohort than the commonly reported 20–30% [ 7 , 8 , 10 , 12 , 18 , 19 , 20 ], the incidence rate did not differ between patients who were treated with immunotherapy in the first-line treatment or after previous treatment with VEGFi. For patients with previous thyroid dysfunction on VEGFi we found a non-significant trend of increased irT risk (HR = 2.14, p = 0.08).…”
Section: Discussioncontrasting
confidence: 87%
“…The relationship between these phenomena and treatment-related thyroid dysfunction in RCC patients requires further research. The timing of thyroid dysfunction was similar to that reported in previous studies [ 12 , 19 ].…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Hypothyroidism is the most common endocrine irAE, occurring in around 10% of patients receiving anti-PD-1–PD-L1 antibodies as monotherapy and in up to 20% receiving ipilimumab plus nivolumab. Prior to hypothyroidism, approximately half of all patients have destructive thyroiditis resulting in excessive thyroid hormone secretions (thyrotoxicosis), which is often asymptomatic 77 . The median time to onset is approximately 6 weeks after commencing therapy, although hypothyroidism can arise at any time on therapy 78 .…”
Section: Chronic Iraesmentioning
confidence: 99%